Dynamic simulation of loss of insulation vacuum event for ITER cryodistribution system. (September 2020) - Muralidhara, Srinivasa; Vaghela, Hitensinh; Patel, Pratik; Shukla, Vinit; Choukekar, Ketan
Highlights: Multi-process cryolines may undergo "Loss of Insulation Vacuum Event or Fire". Safety devices are installed to protect process volume during failure scenarios. A relief header is installed to collect the discharge from safety devices. The backpressure is essential to validate size and type of selected safety devices. Various process models are developed and the results are presented. Based on the results balanced bellow type of safety device type is recommended. Abstract: Auxiliary Cold Boxes (ACBs) of ITER cryodistribution system has multiple cryogenic process volumes as well as interfaces with cryolines having isolated vacuum spaces. Cryogenic process volumes inside a single vacuum space have different temperature levels, 4 K and 80 K as well as different operating pressure, 5 bar(a) and 18 bar(a). Cryogenic process volumes including interfacing cryolines are protected with safety devices (e.g. Safety Relief Valves (SRVs) and Rupture Discs (RDs)). In an accidental event like Loss of Insulation Vacuum (LIV) of any particular vacuum space, incidental heat load of order of 6.5 kW/m 2 results in rapid pressurization of cryogenic process volume; considering safety of cryolines excess pressure is to be relieved through SRVs. As per nuclear safety requirements of ITER, maximum helium inventory inside tokamak building is restricted; hence, a common relief header is necessary to collect SRVs discharge and carry it outside tokamak building. Due to long length of relief header, required information regarding backpressure on SRVs is not known in advance. The backpressure is a function of geometric condition of relief header, process condition of relieving process volume and relieving mass flow rate. The estimation of backpressure considering steady-state condition and maximum mass flow rate through all connected SRVs may result in a conservative and unrealistic value. Therefore, a dynamic simulation of safety relief event along with complete model of process volume, boundary conditions as well as geometric detail of relief header is performed using pressure-flow solver model in Aspen HYSYS®. Two simulation approaches are considered for present study to estimate backpressure (i) Steady state maximum mass flow model, which considers maximum relieving mass flows of SRVs computed from code (EN13648-3) (ii) Dynamic mass flow model, which considers the size of SRVs from code and process pressure, mass flow evolve with time based on heat load applied on process volumes. The results of backpressure from two simulation approaches are discussed and outcome of study is summarized.